The Sharing economy: the problem of a shared definition (European journal of volunteering and community-based projects, 2022)
The sharing economy is founded on pooling and exchanging services, goods, resources, time, skills, and knowledge in order to reduce the costs and, at the same time, to reduce or eliminate the intermediaries. This phenomenon has increased in importance in recent years but there is no single definition in the literature, rather there are different terms to define the  general concept. The  aim of the paper is therefore to identify the different definitions developed in doctrine in order to finally understand the causes that led to the crisis of the linear economy in favour of the circular economy.
Keywords: Circular economy; Definition; Frugal innovation; Linear economy; Sharing economy